Size matters? : The relation between population size and democracy - Goren, Ran (Helsingin yliopisto, 2017)
Population size is one of the most discussed topics historically in its relation to democracy. Interestingly, however, despite the plethora of debates and studies there seem to be little academic consensus on the topic, both theoretically and empirically. On the one hand, early theorists such as Aristotle, Plato, Rousseau, and Montesquieu, have considered a small population size as indispensable for a democracy, for utilities such as the citizens’ ability to participate, or comprehend the common affairs. On the other hand, later theorists have stressed the utility of large population size to democracy, due to an increased likelihood for a diversity of opinions, and thus more checks, balances, and safeguards against factions’ tyranny and minority abuse. In a similar manner, in contemporary studies there is a common notion of a formula that ‘small is democratic’, mainly referring to the larger share of representative democracies among small states in comparison to larger states. Contrastingly, several studies have highlighted other ‘informal’ and arguably detrimental impacts of small size on democracy, such as lack of political diversity, high personalization, weak separation of authorities, and extensive patronage. This state-of-art, in which there is a predominant academic disagreement about the relation between size and democracy, despite many years of studying and argumentation, calls for a further study of the topic. Accordingly, the purpose of this study is to delve into the abundant content on the topic, in order to produce a qualified understanding of the possible relation between population size and democracy. The methodology of this study is a theoretical analysis, based on critical literature review of the contents on the topic. These are assessed using a lengthily-delineated definition of democracy, conceptualizing it as a system yet to be realized in our time, in which all people hold an adequate and equal capacity to make choices in governance. Using this definition, it is concluded that population ...